Mass-spectrometric study of thermal desorption processes at vacuum heating of lithium iodide used to Lil(Eu) crystal growing - Sofronov, D.S.; Voloshko, A.Yu.; Shishkin, O.V. (Functional Materials, 2007)
The thermal desorption at vacuum heating of fused Lil used to grow crystals has been studied using mass spectrometry. Water has been found to be released at 30-100 and 100-170°C due to decomposition of the residual hydrate as well as oxygen above 200°C. The oxygen release may be caused by decomposition of an impurity formed due to the hydrate dehydration.